2013
DOI: 10.1186/1742-4690-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Interferon block to HIV-1 transduction in macrophages despite SAMHD1 degradation and high deoxynucleoside triphosphates supply

Abstract: BackgroundInterferon-α (IFN-α) is an essential mediator of the antiviral response, which potently inhibits both early and late phases of HIV replication. The SAMHD1 deoxynucleoside triphosphate (dNTP) hydrolase represents the prototype of a new antiviral strategy we referred to as “nucleotide depletion”. SAMHD1 depletes dNTP levels in myeloid cells below those required for optimal synthesis of HIV viral DNA. HIV-2 and its SIVsm and SIVmac close relatives encode a protein termed Vpx, which counteracts SAMHD1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 68 publications
(76 reference statements)
4
34
0
Order By: Relevance
“…Treating the cells with a cocktail of antibodies against type-I IFN and the type-I IFN-R partially restored the ability of Vpx to induce SAMHD1 degradation and facilitated infection, suggesting that signaling through the type-I IFN-R rendered Vpx unable to induce SAMHD1 degradation. This result is similar to that of Dragin et al 45 who found that in differentiated THP1 cells, type-I IFN renders Vpx unable to induce SAMHD1 degradation. The mechanism by which type-I IFN blocked the Vpx-induced degradation of SAMHD1 is unclear.…”
supporting
confidence: 91%
“…Treating the cells with a cocktail of antibodies against type-I IFN and the type-I IFN-R partially restored the ability of Vpx to induce SAMHD1 degradation and facilitated infection, suggesting that signaling through the type-I IFN-R rendered Vpx unable to induce SAMHD1 degradation. This result is similar to that of Dragin et al 45 who found that in differentiated THP1 cells, type-I IFN renders Vpx unable to induce SAMHD1 degradation. The mechanism by which type-I IFN blocked the Vpx-induced degradation of SAMHD1 is unclear.…”
supporting
confidence: 91%
“…It is known that HTLV-1 infection causes local and systemic inflammation, and perhaps this inflammatory response alters SAMHD1 expression. In addition, SAMHD1 expression has been shown to be regulated by interferons (86)(87)(88)(89). We recently showed that expression of the HTLV-1 p30 protein dampens interferon responses in monocytes and dendritic cells by blocking the expression of interferon-responsive genes (40).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-ε had a slight ability to either promote (line 1) or inhibit (line 2) HIV infection of PMA-treated THP-1 cells, whereas IFN-α efficiently blocked infection ( Figure 1E), suggesting that pathways involved in the inhibitory activity of these two IFNs are not identical. SAMHD1 is a myeloid cell restriction factor that is induced in specific cell types by type I IFNs (34,35). To determine whether SAMHD1 plays a role in the IFN-ε antiviral activity, we assessed the effect of IFN-ε on HIV infection of THP-1 with an shRNA stable knockdown of SAMHD1 (36).…”
Section: Ifn-ε Blocks Hiv-1 Infection Of Primary Macrophagesmentioning
confidence: 99%